The correlation of Osteoporosis with Trigeminal Neuralgia: a Literature Review - Lousada, Lívio Martins; Nunes, Melyssa Maria Fernandes da Rocha; Soares, Ana Clara Mendes; Azevedo, Marina Pinheiro Uchoa; Pinheiro, Giulia Rebouças; Filho, Otavio Pereira da Silva; Coutinho, Isadora Pinheiro; Moura, Lucas Eliel Beserra (Headache Medicine, 2023)
Full abstract in PDF.